Damming water influences the structure, composition and functions of adjacent savannahs - Santiago do Vale, Vagner; de Oliveira, Ana Paula; do Prado-Junior, Jamir Afonso; Ribeiro Londe, Patrícia; Nascimento, Diego Raymundo (Instituto de Ecología, A.C., 2017)
Dams are important to human wellbeing; however, they can cause various environmental changes. In the cerrado stricto sensu, waters from the reservoir modify water supply in the soil and can affect species establishment. It is argued that species adapted to high water availability can establish close to river banks and water reservoirs and their characteristics are different from those of species from the cerrado stricto sensu. These characteristics could be more similar to those of species from riparian forests, with higher values of height and basal area. Thus, we aim to analyze changes in an area of the cerrado stricto sensu, 35 years after the construction of a hydroelectric dam. We tested different parameters to determine these changes, including richness, diversity, individual height and basal area (using the square-point method), with individuals <1 m, individuals >1 m, and Bromeliaceae (using the plot method) in three sectors close to the artificial lakeshore (0 m - 20 m, 40 m - 60 m, and 80 m - 100 m away from the water). Using species diversity, we also compared the species functional group within these sectors. Sectors closer to the dam acted as an edge, presenting lower basal area and individual’s height, but species with different traits compared to those of a cerrado stricto sensu area.